HUBUNGAN KADAR SGPT (SERUM GLUTAMIC PYRUVIC TRANSAMINASE) DENGAN TITER WIDAL ANTIGEN O Salmonella typhiii Pada PENDERITA DEMAM TYPHOID - Widyastuti, Rahma (Universitas Muhammadiyah Surabaya)
HUBUNGAN KADAR SGPT (SERUM GLUTAMIC PYRUVIC TRANSAMINASE) DENGAN TITER WIDAL ANTIGEN O Salmonella typhiii Pada PENDERITA DEMAM TYPHOIDÂ Rahma Widyastuti, S.Si., M.Kes.Prodi D3 Analis Kesehatan UM SurabayaAbstractTyphoid fever is an acute systemic infectious disease caused by Salmonella typhiii. Salmonella typhii O antigen that endotoxin has led to the emergence of symptoms of fever, so the decreased immune. At the time this condition titer Widal O antigen positive (low - high). When the immune system decreases S.typhii easy entry into the organs of the body including the liver, causing increased ALT levels. Correlational type of research is one way that the data in the form of secondary data taken Bhayangkara Hospital HS Samsoeri Mertojoso Surabaya East Java Police. The population in this study were patients with typhoid fever who examined levels of SGPT (Serum Glutamic Pyruvic transaminase) and Widal titer of 100 samples. The samples selected while the inclusion criteria of patients with typhoid fever, typhoid fever patients were examined Widal, Typhoid Fever Patients Patients who widalnya titer 1/80 and 1/160 O antigen of Salmonella typhii and SGPT levels checked as many as 50 samples. From the results of alanine aminotransferase levels in titer Widal O antigen of Salmonella typhii is known that the average ALT was 55.64 U / l. Statistical analysis with Chi - Square showed no relationship between titer Widal O antigen of Salmonella typhii with ALT levels in patients with typhoid fever, with a significant value of less than 0.05 (5%).Â Keyword : Salmonella typhii, SGPT, WidalÂ